The Intervention of Job Satisfaction in Influence of Compensation and Work Environment on Employee Engagement at Pertamina Fuel Station Operators in Regional III - Wahyuni, Sri; Levyda, Levyda (Yayasan Riset dan Pengembangan Intelektual, 2026)
Many organizations, including the operator of the Pertamina MOR III fuel station, face challenges related to employee engagement, which are reflected in low work morale and high turnover intention that may ultimately reduce the quality of customer service. Employee engagement is influenced by several organizational factors, particularly compensation, work environment, and job satisfaction, where fair and appropriate compensation as well as a supportive and conducive work environment tend to increase employees’ job satisfaction and encourage stronger engagement at work. Therefore, this study aims to examine the effect of compensation and work environment on employee engagement, both directly and indirectly, with job satisfaction as a mediating variable. This quantitative study uses a sample of 393 respondents proportionately distributed across each sales area, with data collected through a questionnaire. Data analysis was conducted using SmartPLS 4.0 software and the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach.